Acceptance and benefits of two different strategies to timely integrate specialist palliative care into routine cancer care: a randomized pilot study - Ullrich, Anneke; Wilde, Svenja; Müller, Volkmar; Sinn, Marianne; Gebhardt, Christoffer; Velthaus, Janna-Lisa; Gerlach, Christina; Bokemeyer, Carsten; Oechsle, Karin (Oncology research and treatment, 2022)
BACKGROUND/AIMS: The aim of this study is to investigate the acceptance and benefits of two different strategies to timely integrate specialist palliative care (SPC) in routine cancer care: commonly recommended early SPC counselling versus an informational brochure plus SPC counselling upon patients' request. - METHODS: Patients diagnosed with incurable cancer within the last 6-12 weeks were sequentially randomized. Endpoints were acceptance of the two strategies after 3 months as well as the use of SPC counselling and psychosocial support, presence of advance directives, palliative care outcome (Integrated Palliative care Outcome Scale [IPOS]), and psychosocial distress (Distress Thermometer [DT]) after 3 and 6 months. In a qualitative part, SPC consultations were analyzed using a content analysis. - RESULTS: Overall, 43 patients received SPC counselling and 37 a brochure with SPC counselling on demand. In the brochure group, only one patient later registered for SPC counselling from own initiative. SPC timing was appropriate in 70% of patients (75% counselling/61% brochure, n.s.). Sufficiency, helpfulness and relevance of information, provision of security, and help with finding contacts for specific support were perceived adequate in both groups. No significant differences were found regarding potential effects of the interventions on IPOS or DT after 3 and 6 months. The use of psychosocial support was comparable between the groups and 4 patients had new advance directives (3 counselling/1 brochure). Five key themes of SPC consultations were identified: symptoms, rapport, coping, illness understanding, and advance care planning. - CONCLUSIONS: Both SPC integration strategies were well accepted. However, patients seem not to benefit from a brochure in terms of initiating SPC counselling timely after a palliative cancer diagnosis.
Published online: November 24, 2021
Gesehen am 02.09.2022